Pengaruh Kualitas Produk, Persepsi Harga, Social Media Marketing, Online Customer Review Terhadap Keputusan Pembelian: (Studi Pada Konsumen Produk Fashion Jiniso di Marketplace Shopee) - Suzy Widyasari; Kemalasari, Putri (Kajian Bisnis Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2024)
The development of the internet has significantly transformed nearly all aspects of human life, especially in shopping habits. This phenomenon is reflected in the shift from conventional or offline shopping to online shopping, driven by advances in digital technology. Consequently, this has created competition between online and offline retailers in their efforts to maintain and expand their market share. Therefore, effective marketing strategies are needed to reach consumers maximally and enhance purchasing decisions. The aim of this study is to examine and analyze how product quality, price perception, social media marketing, and online customer reviews influence purchasing decisions. The consumers of Jiniso fashion products are the subjects of this study. This research is quantitative and uses purposive sampling technique. The sample consists of 100 respondents, obtained through a Google Forms questionnaire. In this research, data testing techniques include validity testing with factor analysis based on KMO and loading factor values, as well as reliability testing with Cronbach's alpha analysis. Data analysis in this study uses multiple linear regression tests, the coefficient of determination, F-test, and t-test. Data is processed using IBM SPSS 26 software. The research results indicate that product price perception, product quality, social media marketing, and online customer reviews have a positive and significant influence on purchasing decisions.